Slump - Waltman, Kevin (2014)
Derrick "D-Bow" Bowman thought sophomore year would be easier, but his girlfriend Jasmine leaves him for putting too much focus on basketball, the jump shot he worked on all summer is not working, and his father has a heart attack, forcing Derrick to accept that basketball cannot be his only priority.
Keywords: Basketball stories; High schools -- Fiction; Schools -- Fiction; African Americans -- Fiction